The effect of primary drug resistance on CD4+ cell decline and the viral load set-point in HIV-positive individuals before the start of antiretroviral therapy. (1st February 2019) - Schultze, Anna; Torti, Carlo; Cozzi-Lepri, Alessandro; Vandamme, Anne-Mieke; Zazzi, Maurizio; Sambatakou, Helen; De Luca, Andrea; Geretti, Anna M.; Sonnerborg, Anders; Ruiz, Lidia; Monno, Laura; Di Giambenedetto, Simona; et al.
Abstract : Objective: To evaluate the effect of primary resistance and selected polymorphic amino-acid substitutions in HIV reverse transcriptase and protease on the CD4 + cell count and viral load set point before the start of antiretroviral treatment. Design: Prospective cohort study. Methods: A total of 6180 individuals with a resistance test prior to starting antiretroviral treatment accessing care in HIV clinics across Europe who had at least one viral load and one CD4 + test available were included in the analysis. The impact of amino-acid substitutions variants on viral load and CD4 + trends was investigated using linear mixed models. Clusters of mutations were studied using principal component analysis. Results: Overall, the detection of any primary resistance was not associated with either the speed of CD4 + cell decline or the viral load set point. However, transmitted nucleoside reverse transcriptase inhibitor and protease inhibitor resistance appeared to be weakly associated with lower viral load set points, as were the polymorphic G16E or Q92K protease mutations. There was some evidence suggesting that these effects varied according to HIV subtype, with the effects of transmitted nucleoside reverse transcriptase inhibitor and protease resistance being particularly marked among individuals with a subtype B virus. A cluster of five polymorphic protease substitutions at position 20, 13, 36, 69 and 89 was associated with less steep CD4 + cell declines and lower viral load set points. Conclusion: Although we found little evidence for an association between primary resistance and CD4 + speed of decline and viral load set point, the potential role of polymorphic protease (alone or in clusters) and their interplay with HIV subtype needs to be further evaluated. Abstract : Supplemental Digital Content is available in the text